Прообрази просторів невизначеності. Прості підпростори - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A semantic hypothesis and a demand on succession of the development of uncertainty apparatus are formulated. The restriction problem is described. The problem consists in having learned to exclude from consideration some points of uncertainty space. A conjecture that the restriction problem solution is connected with construction of subspaces is considered. The notions of uncertainty space prototype and subspace (as a particular case of prototype) is built with the help of methods of N. Bourbaki’s theory of mathematical structures. Examples of subspaces are given.